Examining the impact of labour turnover on organisational performance - Bulya Maria Antonny Cindy (Uganda Christian University, 2024)
The research examined the impact of labor turnover on organisational performance at Guaranty trust bank Uganda. The study used a cross-sectional approach, combining both qualitative and quantitative methods. Cross-sectional studies provide a snapshot of a particular aspect within a population at a single point in time, offering a simple form of descriptive or observational epidemiology conducted on representative samples. A descriptive design was employed, with 100 respondents selected from Guaranty Trust bank. Employees were chosen randomly, and those who agreed to participate completed questionnaires along with the company's administrators. The results revealed that turnover negatively impacts organisational performance, and management should enhance training programs to improve employees' job satisfaction.
This study investigates the impact of labor turnover on organizational performance at Guaranty Trust Bank Uganda using a cross-sectional design. By employing both qualitative and quantitative methods, data were collected from 100 randomly selected employees, including administrators, through questionnaires. The findings indicate that labor turnover adversely affects organizational performance. The study recommends enhancing training programs to increase employee job satisfaction, thereby reducing turnover and improving overall performance.